1981
DOI: 10.1037/0003-066x.36.9.972
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the history of social psychology.

Abstract: A general survey of the metatheoretical perspectives arid theory-research areas that constitute the main history of U.S. social psychology reveals the individual to be at the center of the most widely engaging and influential schools and movements. Conversely, theories and research programs that have dealt generally with group or collective phenomena, employing interdependence or other "relational" concepts, have had a less continuous and long-term impact on the field. The individuocentric bias derives mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
8

Year Published

1982
1982
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 59 publications
0
61
0
8
Order By: Relevance
“…Normative beliefs are important both in the regulation of aggressive behavior [Huesmann, 1988;Zumkley, 1984], and in determining people's reactions to harmful incidents [Pepitone, 1976[Pepitone, , 1981. Peer-report studies have shown that children and adolescents who believe that it is wrong to carry out an aggressive act are perceived as less aggressive compared with those who believe aggression is an appropriate response [Erdley and Asher, 1998;Henry et al, 2001;Salmivalli and Voeten, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Normative beliefs are important both in the regulation of aggressive behavior [Huesmann, 1988;Zumkley, 1984], and in determining people's reactions to harmful incidents [Pepitone, 1976[Pepitone, , 1981. Peer-report studies have shown that children and adolescents who believe that it is wrong to carry out an aggressive act are perceived as less aggressive compared with those who believe aggression is an appropriate response [Erdley and Asher, 1998;Henry et al, 2001;Salmivalli and Voeten, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Conforme salientado no presente relatório, a Teoria da Representação Social teve origem na França, começando a ser divulgada nos Estados Unidos a partir da década de 1960. Esse fato pode justificar o motivo pelo qual muitos dos autores citados tenham fundamentado suas pesquisas no conceito de estereótipo presente na teoria cognitivista que, segundo Pepitone (1981), possui base ontológica positivista, tendo como característica a busca por leis universais capazes de explicar o comportamento social. Essa corrente de pesquisa, tradicional na América do Norte, desconsidera as influências de fatores socioculturais na formação da percepção da realidade, considerando a existência de uma única realidade verdadeira .…”
Section: A Imagem Do Profissional Contábil Em Pesquisas Empíricasunclassified
“…A number of critics have complained about the asocial nature of contemporary American social psychology (e.g., Farr, 1996;Graumann, 1986;Pepitone, 1981;Post, 1980;Stroebe, 1979). Unfortunately, few critics specify what they take to have been neglected by American social psychology, other than cryptic references to "trans-or supra-individual structures" (Graumann, 1986), "relationalism" (Pepitone, 1981), or "the relationship between the individual and the community (or society)" (Farr, 1996).…”
Section: Individualism and The Social In Early American Social Psychomentioning
confidence: 99%
“…Unfortunately, few critics specify what they take to have been neglected by American social psychology, other than cryptic references to "trans-or supra-individual structures" (Graumann, 1986), "relationalism" (Pepitone, 1981), or "the relationship between the individual and the community (or society)" (Farr, 1996). In this paper I try to articulate the respect in which early American social psychologists did recognize social forms of cognition, emotion, and behavior as the subject matter of a distinctively social psychology: the original conception of the social that came to be neglected by later generations of American social psychologists.…”
Section: Individualism and The Social In Early American Social Psychomentioning
confidence: 99%